Beneficial land use change: Strategic expansion of new biomass plantations can reduce environmental impacts from EU agriculture. (January 2020) - Englund, Oskar; Börjesson, Pål; Berndes, Göran; Scarlat, Nicolae; Dallemand, Jean-Francois; Grizzetti, Bruna; Dimitriou, Ioannis; Mola-Yudego, Blas; Fahl, Fernando
Highlights: Substantial potential for mitigating assessed impacts by strategic perennialization. Highest mitigation potential found for accumulated SOC losses. Priority areas for strategic perennialization scattered across EU. Main ``hot spots'': Denmark, western UK, The Po valley in Italy, and the Danube basin. 10–46% of current annual crops in EU within priority areas. Abstract: Society faces the double challenge of increasing biomass production to meet the future demands for food, materials and bioenergy, while addressing negative impacts of current (and future) land use. In the discourse, land use change (LUC) has often been considered as negative, referring to impacts of deforestation and expansion of biomass plantations. However, strategic establishment of suitable perennial production systems in agricultural landscapes can mitigate environmental impacts of current crop production, while providing biomass for the bioeconomy. Here, we explore the potential for such "beneficial LUC" in EU28. First, we map and quantify the degree of accumulated soil organic carbon losses, soil loss by wind and water erosion, nitrogen emissions to water, and recurring floods, in ∼81.000 individual landscapes in EU28. We then estimate the effectiveness in mitigating these impacts through establishment of perennial plants, in each landscape. The results indicate that there is a substantial potential for effective impact mitigation. Depending on criteria selection, 10–46% of the land used for annual crop production in EU28 is located in landscapes that could be considered priority areas for beneficial LUC. These areas are scattered all over Europe, but there are notable "hot-spots" where priority areas are concentrated, e.g., large parts of Denmark, western UK, The Po valley in Italy, and the Danube basin. While some policy developments support beneficial LUC, implementation could benefit from attempts to realize synergies between different Sustainable Development Goals, e.g., "Zero hunger", "Clean water and sanitation", "Affordable and Clean Energy", "Climate Action", and "Life on Land".